Incidence and Mortality of Acute Respiratory Distress Syndrome in Patients With Burns: A Systematic Review and Meta-Analysis - Wang, Baoli; Chenru, Wei; Jiang, Yong; Hu, Lunyang; Fang, He; Zhu, Feng; Yu, Qing; Zhu, Banghui; Wu, Guosheng; Sun, Yu; Xia, Zhaofan (Frontiers in Medicine, 2021)
Objective: We conducted a systematic review and meta-analysis to comprehensively estimate the incidence and mortality of acute respiratory distress syndrome (ARDS) in overall and subgroups burns patients. Data Sources: Pubmed, Embase, the Cochrane Library, CINAHL data bases and China National Knowledge Infrastructure database were searched until September 1, 2021. Study Selection: Articles which report study data on incidence or mortality of ARDS in burn patient were selected. Data Extraction: Two researchers independently screened the literature, extracted data, and assessed the quality. We performed a meta-analysis of the incidence and mortality of ARDS in burn patients by using a random effects model, which made subgroup analysis according to the study type, inclusion (mechanical ventilation, minimal burn surface), definitions of ARDS, geographic location, mean age, burn severity and inhalation injury. Primary outcome was the incidence and mortality of ARDS in the burn patients and secondary outcomes were incidence for different subgroups. Data Synthesis: Pooled weighted estimate of the incidence and mortality of ARDS in burn patient were 0.24 [95% confidence interval (CI) 0.20–0.28] and 0.31 [95% CI 0.18-0.44]. For the patients with mechanical ventilation (incidence=0.37), diagnosed by Berlin definition (incidence=0.35), and with over 50% inhalation injury proportion (incidence=0.41), the incidences of ARDS were obviously high than the overall burn patients. The burn patients came from western countries and with inhalation injury have significantly higher incidence of ARDS compared with those came from Asian /African countries (0.28 vs 0.25) and without inhalation injury (0.41 vs 0.24). Conclusion: This systematic review and meta-analysis revealed that the incidence of ARDS in burn patients is 24%, but the mortality is as high as 31%. The incidence rates are related to mechanical ventilation, location, and inhalation injury. The burn patients from western countries and with inhalation injury have significantly higher incidence of patients from Asian/African countries and without inhalation injury.